Implied Volatility and Smile - Rojček, Jakub; Pígl, Jan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2008)
In this work author speaks a little in generic about financial derivatives. Then he derives the famous Black-Scholes formula using less precise mathematical apparatus. Afterwards, he will analyze a few volatility models and their applications for creating volatility surface, which is the main goal of both theoreticians and practitioners. As we will see, the theory is yet very deep but unconsolidated. Nevertheless, praxis has gained some nearly sufficient approaches.
Vedoucí práce: Jan Pígl
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2008
Rok obhajoby 2008
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses